Altered cognition and anxiety in adolescent offspring whose mothers underwent different-pattern maternal sleep deprivation, and cognition link to hippocampal expressions of Bdnf and Syt-1 - Wei, Ru-Meng; Zhang, Yue-Ming; Li, Yun; Wu, Qi-Tao; Wang, Ya-Tao; Li, Xue-Yan; Li, Xue-Wei; Chen, Gui-Hai (Frontiers in Behavioral Neuroscience, 2022)
Background Inadequate sleep during pregnancy negatively affects the neural development of offspring. Previous studies have focused on the continuous sleep deprivation (CSD) paradigm, but the sleep pattern during late pregnancy is usually fragmented. Objective To compare the effects of CSD and fragmented sleep deprivation (FSD) in late pregnancy on emotion, cognition and expression of synaptic plasticity-related proteins in offspring mice. Methods Pregnant CD-1 mice were either subjected to 3/6 h of CSD/FSD during gestation days 15-21, while those in the control group were left untreated. After delivery, the offspring were divided into five groups, i.e., control (CON), short or long CSD (CSD3h, CSD6h), short or long FSD (FSD3h, FSD6h). When the offspring were 2 months old, the anxiety-like behavior level was tested using the open field (OF) and elevated plus maze (EPM) test, and spatial learning and memory were evaluated using the Morris water maze (MWM) test . The hippocampal expression of brain-derived neurotrophic factor (Bdnf) and synaptotagmin-1 (Syt-1) was determined using RT-PCR and western blotting. Results The CSD6h, FSD3h and FSD6h had longer latency, fewer center times in the OF test, less open arms time and fewer numbers of entries in the open arms of the EPM, longer learning distance swam and lower memory percentage of distance swam in the target quadrant in the MWM test, and decreased BDNF and increased Syt-1 mRNA and protein levels in the hippocampus. Compared to the CSD6h, the FSD3h and FSD6h had longer distance swam, lower percentage of distance swam in the target quadrant, and decreased BDNF and increased Syt-1 mRNA and protein levels in the hippocampus . Conclusions The results suggested that maternal sleep deprivation during late pregnancy impairs emotion and cognition in offspring, and FSD worsened the cognitive performance to a higher extent than CSD. The observed cognitive impairment could be associated with the altered hippocampal expression of Bdnf and Syt-1genes.